Some aspects of morphobiology, conservation of resource potential, crop cultivation and harvesting of raw materials of promising Ferula species - Khodzhimatov, Olim Kaharvich; Bussmann, Rainer W; Khamraeva , Dilovar T (Ethnobotany Research and Applications, 2021)
Background: The purpose of this work was to increase scientific information against the background of increasing anthropogenic pressure on nature, which causes irreparable damage to the flora, especially the most sought-after raw materials (especially resins). An improvement of the situation would require cultivating wild species and establishing new plantations that combine the most effective method of cultivating and producing raw material (resins) from Ferula tadshikorum Pimenov and Ferula foetida (Bunge) Regel, in Uzbekistan. Methods: In the present note we reviewed the existing literature for Uzbekistan and the surrounding areas to compile guidelines for the production of Ferula. Results: In total, 5 different fractions of Ferula resin can be obtained, differing from each other in quality and organoleptic properties, which affects the grade and cost of the final product. The raw materials of both species of Ferula are marketed under the common commercial name "assafetida resin. After the collection of raw materials, the roots are again covered with soil. However, according to our observations, after such a long harvest and many cuts applied, the restoration of plants does not occur, the plants die. Therefore, we recommend stop collecting after receiving the Khalva-donak fraction, because this will result in better and more expensive raw materials for the market, and at the same time, will help to preserve and restore plants for subsequent years of harvesting. Conslusion: When harvesting raw materials from underground parts of two species of Ferula, it is of paramount importance to leave a mandatory 20-25% of plants intact to produce seed material. Being monocarpics, both species produce seeds only once during their ontogenesis. The obtained seed material helps to maintain the population and will also serve for further expansion of plantations. Key words: Ferula tadshikorum, Ferula foetida, medicinal plant, resin, yield, plantations, Uzbekistan.